Endogenous Auxin Content Contributes to Larger Size of Apple Fruit - Bu, Haidong; Yu, Wenquan; Yuan, Hui; Yue, Pengtao; Wei, Yun; Wang, Aide (Frontiers in Plant Science, 2020)
Fruit size is an important economic trait that is controlled by multiple genes; However, the regulatory mechanism for fruit size remains poorly understood. A bud sport variety of ‘Longfeng’ (LF) apple (Malus domestica) was identified and named ‘Grand Longfeng’ (GLF). The fruit size of GLF is larger than LF and both varieties are diploid. We found that the cell size in GLF fruit was larger than LF. Then, we compared the fruit transcriptomes of the two varieties using RNA-Seq technology. A total of 1166 differentially expressed genes (DEGs) were detected between GLF and LF fruits. The KEGG analysis revealed that the phytohormone pathway was the most enriched, in which most of the DEGs were related to auxin signaling. Moreover, the endogenous auxin levels of GLF fruit was higher than LF. The expression of auxin synthetic genes, including MdTAR1 and MdYUCCA6, were higher in GLF fruit than LF. Collectively, our findings suggest that auxin plays an important role in fruit size development.